The last voyage of Capt. Sir John Ross . to the Arctic regions for the discovery of a north west passage : performed in the years 1829-30-31-32 and 33 : to which is prefixed an abridgement of the former voyages of Captns. Ross, Parry & other celebrated navigators to the northern latitudes : compiled from authentic information and original documents transmitted by an officer attached to the last expedition - Huish, Robert, 1777-1850. (London : Printed for the proprietors : Published by John Saunders, 1835)
"On the position of the north magnetic pole. (Supplement)": 44 p. at end. "Dictionary of the Esquimaux language": p. [697]-703. Added engraved t.p. dated 1834. Mode of access: Internet.